(untitled) (TAJ: Journal of Teachers Association, 2018)
This quasi experimental study was designed to evaluate antibacterial activity of chemically synthesized silver nanoparticles (AgNPs) from silver nitrate (AgNO3) solutions on gram negative bacteria like E.Coli using disc diffusion method. Different concentrations of AgNPs, AgNO3 and reference drug ciprofloxacin were used to find out the antibacterial activity which revealed that AgNPs possessed significant antibacterial effect compared to AgNO3 solutions but relatively less antibacterial effect than that of ciprofloxacin. So chemical synthesis guided AgNPs may have some antibacterial effects. TAJ 2016; 29(2): 37-41